Antecedents and consequences of market orientation in international B2B market: role of export assistance as a moderator. Issue 6 (13th January 2021) - Mostafiz, Md Imtiaz; Sambasivan, Murali; Goh, See Kwong
Abstract : Purpose: The significance of market orientation (MO) in industrial marketing literature is immense. Separately, the role of dynamic managerial capability (DMC) as an individual-level capability has been found to be beneficial to business-to-business (B2B) transactions. However, the assessments of DMC as the antecedent to complement MO in achieving firm performance are rare. To address this knowledge gap, this study builds upon a research framework on the DMC theory and MO literature. Additionally, this study aims to investigate how export assistance avails MO-firm performance relationship and assists entrepreneurs to thrive in the international market. Design/methodology/approach: The research was conducted among the entrepreneurial export manufacturing firms in the apparel industry in Bangladesh. Structural equation modelling was used to investigate the hypothesized relationship among 329 firms. Findings: Two attributes of DMC, namely, managerial social capital and managerial cognition of entrepreneurs improve the MO process of export manufacturing firms. MO mediates the relationship between DMC and firm performance. Additionally, export assistance positively moderates the relationship between MO and the financial performance of the firm. Originality/value: MO requires complementary capabilities to realize the value of it efficiently. This study strongly advocates entrepreneurs to nurture DMC to leverage MO and capitalize on emerging opportunities by productively using export assistance. Firms in the emerging economies often suffer from resource-scarcity and export assistance mitigates barriers to expand international operations and yield financial liberty to the firms operating in the international B2B market.